PENGARUH PROFESIONALISME, PELATIHAN DAN MOTIVASI TERHADAP KINERJA NURSE DAN CAREGIVER INDONESIA - Reni Kristina Arianti (Universitas Mercu Buana, 2013)
Abstract: Japan Economic Partnership Agreement (IJEPA) is the only bilateralcooperation framework managed by Indonesia, which includes the movement of naturalpersons. Moreover, the Government of Japan gives opportunities for medical personnelespecially Indonesian nurse and caregiver to work in Japan. Therefore, the Governmentof Indonesia requires to ake the higest possible advantages of the cooperation programby preparing Indonesian nurse and caregiver to compete with those of other countries.Thus Indonesia not only has skilled and qualified workforce, but also able to maintainits existence in the international world. This research is aim to demonstrate the effectsof professionalism, training, and motivation on the performance of Indonesian nurseand caregiver. In this case, we employ multiple regression model by taking variables ofprofessionalism (X1), training (X2), motivation (X3) as the independent variables andperformance of Indonesian nurse and caregiver (Y) as the dependent variable. Thereseach population is defined as the Indonesian nurse and caregiver who work in Japanespecially Osaka, Kyoto and Tokyo and the sample is selected using purposivesampling based on Slovin formula. Based on the results, we conclude thatprofessionalism has positive effect on the performance and can be proven to be true, Inaddition the training has positive effect on the performance and can be proven to betrue. Finally, motivation has positive effect on the performance and can be proven to betrue.Keywords: Professionalism, Training, Motivation, Performance, Nurse, and Caregiver